WORD STRESS ERRORS MADE BY ENGLISH EDUCATION MASTER’S PROGRAM STUDENTS - Yoannes Yuka Krisdianata; Barli Bram (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2022)
This study investigates English Master’s Program students in producing suprasegmental features, namely word stress. The focus is on analysing disyllabic noun-verb words in six video presentations and what are the factors that affect word stress errors from 19 English master program students. The data were obtained from transcribing the videos and selecting the disyllabic noun-verb words from the transcriptions. Furthermore, a questionnaire was used to gather information about students’ background knowledge in learning English, especially linguistics. Qualitative content analysis was employed in this study. From those videos, there were 1,089 disyllabic noun-verb words produced by the students. The stress errors made were 15 words. The stress errors mostly occurred in the first syllable and no word stress. The findings showed the factors that affected the wordstress errors were students’ native language, Bahasa Indonesia. Bahasa Indonesia did nothave word-stress to differ a meaning, only for emphasis. The questionnaire showed that all students were Indonesian and only two of them used English as their native language. The background knowledge and gender had some effects on stress errors, but not vital. The results indicated that students needed to have a deeper understanding of word stress.